Coping strategies in Spanish older adults: a MIMIC model of socio-demographic characteristics and activity level. (1st February 2018) - Rubio, Laura; Dumitrache, Cristina G.; García, Alfonso J.; Cordón-Pozo, Eulogio
ABSTRACT: Objectives: The aim of this study was to analyze the combined effect of socio-demographic characteristics and activity level on coping strategies and to test which of these variables has a greater impact on coping. Method: A sample of 243 men and women aged 55–99 years old was selected from different elderly activity centers in Granada, Spain, using a convenience sampling. Associations between eight coping strategies measured by Coping Strategies Inventory and the above mentioned variables were examined using a Multiple Indicator and Multiple Causes model. Results: Age was negatively related with problem solving, express emotions and social support. Activity level was positively related with problem solving, cognitive restructuring, express emotions and social support and it was negatively associated with social withdrawal. Gender only predicted the scores in self-criticism and living alone was related with higher emotional expression. Participation in creative activities, attending University for the third age and practicing physical exercise were related with differences in the use of several coping strategies. Conclusions: There is a complex relationship between socio-demographic characteristics, activity level and the coping strategies used by the elderly. It is important to understand this relationship in order to identify older adults who use ineffective coping, and to subsequently include them in intervention programs to improve their coping abilities.